If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 5y = 5 Solving -2x + 5y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -2x + 5y + -5y = 5 + -5y Combine like terms: 5y + -5y = 0 -2x + 0 = 5 + -5y -2x = 5 + -5y Divide each side by '-2'. x = -2.5 + 2.5y Simplifying x = -2.5 + 2.5y
| 2(x+2)-3(x-3)=x+7 | | 12(3x-3.25y)=6 | | 12(3x-3.25y)=12(6) | | 0.4p=-9 | | 7m-7+6m-6= | | t^2+8t+15=0 | | 5x^2+25x+20=0 | | -2h-7=28 | | x(9+x)=112 | | 4-23=m-9+18 | | -x^2+1=-5x^2+4x | | 4-23-m-9+18m= | | 9+5r-9r= | | 4x-7-7=-1 | | -15+7+n=-4+16 | | -9r+10r= | | 12t^2-t-6=0 | | 16P^2-36=0 | | -10v+6v= | | 3(x+1)=11+3(2x-3) | | 7-7x=111-35x | | 7p-10p= | | 5+3(2x-3)=6x-(x-3) | | 5x(x+4)=(4x+2)(x+4) | | 3x-8=2(5x+3) | | 5x+8=-18-8x | | 7x-x= | | 3k+24=6 | | 5(2x-4)=3(2x-1)-1 | | 10x-3(x-8)=19-(3x-17) | | 52-7x=2x+15 | | -p+10=-25 |